High‐Precision Ionic Thermocouples Fabricated Using Potassium Ferri/Ferrocyanide and Iron Perchlorate (Adv. Electron. Mater. 5/2022). (17th May 2022) - Jeon, Jei Gyeong; Kim, Hyeong Jun; Shin, Gilyong; Han, Yusu; Kim, Ju Hyeon; Lee, Ju Hwan; Lee, Junho; Lim, Hyeoncheol; Ha, Seulki; Bae, Minwoo; Yoon, Sang‐Hee; Kang, Tae June
Abstract : Ionic Thermocouple Jei Gyeong Jeon, Tae June Kang, and colleagues introduce a new category of thermocouples in the form of ionic thermocouples that involves the ionic conductors of electrolytes in place of the usual electrical conductors as described in article number 2100693 . The ionic thermocouple can easily be miniaturized as demonstrated for the in‐situ temperature measurement of the fluid flowing in the channel of a microfluidic device.